“Looking for a Golden Needle in the Haystack”: Perspectives on Talent Identification and Development in Paralympic Sport - Dehghansai, Nima; Pinder, Ross A.; Baker, Joe (Frontiers in Sports and Active Living, 2021)
Despite rapid increases in research on talent identification and development in able-bodied sports, there remains limited knowledge regarding how talent is identified and developed in Paralympic contexts. The purpose of this study was to capture the perspectives of experts (coaches, high-performance managers, and pathway specialists) working in elite Paralympic sport to better understand how they conceptualize, measure, and develop talent. Eight coaches and three performance directors from six Paralympic sports, along with two pathway specialists from Paralympics Australia participated in semi-structured interviews. The results suggest impairment type and, therefore, classification are key indicators of identification and anticipated success, highlighting the importance of educating talent selectors in these areas. In addition, familial (e.g. overprotectiveness, sporting background) and biopsychosocial factors (e.g. resilience, work-ethic, sport-specific skills, other life commitments) were noted as being influential when selecting athletes. There were concerns regarding the disproportionately low number of female athletes in the system, suggesting a need for new initiatives to support early-entry points for female athletes (e.g., education on the benefits of sport participation, supportive environments). High-performance staff also lacked resources to better understand the nuances associated with different impairments and their implications (physiological response to training, associated psychological stresses from injury, identity change). Recruitment strategies included ‘talent search’ days, collaborations with school programs and rehabilitation centers, and helping local clubs support ‘drop-in’ athletes. However, limited funding impacted the sustainability of programs, resulting in a regular turnover of staff, loss of intellectual property, and a weakened pathway system. Results from this study generated several practical implications and future directions for research.